1996
DOI: 10.1007/s002800050464
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of the platinum drug JM216 following oral administration to cancer patients

Abstract: This study evaluates the metabolic profile of JM216 [bis(acetato)ammine-dichloro(cyclohexylamine) platinum(IV)], the first orally administrable platinum complex, in plasma ultrafiltrates of 12 patients (n = 2-4 time points per patient) following different doses of drug (120, 200, 340, 420, 560 mg/m2). The biotransformation profile was evaluated by high-performance liquid chromatography (HPLC) followed by atomic absorption spectrophotometry (AA). The AA profiles were compared with those previously identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 16 publications
3
71
0
4
Order By: Relevance
“…Our results show that some metabolites previously observed in patients' plasma ultrafiltrates can be observed intracellularly; those being A, JM383, D and JM 118 (Raynaud et al, , 1996. However, JM216 itself was never detected in patients' plasma ultrafiltrates and a late eluting metabolite F was not seen intracellularly and no JM559 could be measured.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Our results show that some metabolites previously observed in patients' plasma ultrafiltrates can be observed intracellularly; those being A, JM383, D and JM 118 (Raynaud et al, , 1996. However, JM216 itself was never detected in patients' plasma ultrafiltrates and a late eluting metabolite F was not seen intracellularly and no JM559 could be measured.…”
Section: Resultsmentioning
confidence: 63%
“…Preclinical studies have shown that multiple administrations give the best anti-tumour responses (McKeage et al, 1994b) and this has been verified in patients, where multiple administrations could overcome the saturability in absorption observed in the single-dose study (McKeage et al, 1994c;Raynaud et al, 1995). It has been shown that JM216 is converted in patients' plasma into at least six different biotransformation complexes and that these biotransformation products are active in vitro and in vivo (Poon et al, 1995;Raynaud et al, 1996). Three of the metabolites present in patients have not yet been identified.…”
mentioning
confidence: 99%
“…Upon administration of satraplatin, a number of metabolites (JM118, JM383, JM518, JM559 and JM149) are formed [43]. Satraplatin and other platinum-based compounds exhibit anti-tumour activity via the formation of DNA crosslinks in vitro [44] which in turn results in specific cellular responses, namely, apoptosis and inhibition of transcription leading to arrest of cell replication [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…It also gives confidence that the exposure achieved in man (and therefore potential anticancer activity) is equivalent to that seen in the mouse models (Raynaud et al, 1997). In contrast to some other recently investigated novel platinum compounds such as satraplatin, AMD473 is not subject to extensive degradative metabolism (McKeage et al, 1995;Raynaud et al, 1996;Judson et al, 2000).…”
Section: Discussionmentioning
confidence: 98%